Morphological Study of Pollen Grains and Seeds in Eight Species from the Family Cruciferae in Iraq (Baghdad Science Journal, 2025)
The shape dimensions and characteristics of pollen grains and seeds have importance in distinguish among species. Therefore, the present study included morphological characteristics of pollen grains and seeds for eight species belonging to eight genera of the family Brassicaceae and these species are: Alliaria petiolata (M.Bieb) Cavara et Grand, Aubrieta parviflora Boiss, Cardamine hirsuta L., Crambe orientalis L., Eromobium aegyptiacum (Spreng.) Schweinf.et Asch.ex Boiss., Parlatoria cakiloidea Boiss., Sterigmostemum sulphureum (Banksetsol.) Bornm. Neotorularia torulosa (Desf.) Hedge & J. Leonard. The pollen grains were studied in morphological and full measurements were taken, the study showed that the majority of the pollen grains was tricolpate and shape was determined to be prolate, sub prolate and prolate spheroidal. In terms of size, the pollen grains of the studied species varied between small size, medium size, the basic surface pattern of the studied pollen grains was reticulate. The study showed that the morphological characteristics of the seeds varied in shape between oblong-elliptic, lenticular- discoid, ovoid, suborbicular and obovoid. The location of hillum was a difference between terminal and basal position and the surface sculpture of the seed surface varied between a longitudinal striate prominent, faintly reticulate, reticulate, pustular, faintly reticulate and pustular and a smooth. The seeds also varied in color and dimensions, existence of wing in the studied species.